Strontium Chloride Modified Nieuwland Catalyst in the Dimerization of Acetylene to Monovinylacetylene - Lu, Jun-Long; Xie*, Jian-Wei; Liu, Hai-Yue; Liu, Ping; Liu, Zhi-Yong; Dai*, Bin (Asian Journal of Chemistry, 2014)
SrCl2 was used as a co-catalyst of CuCl in Nieuwland catalyst and CuCl as the main catalyst, NH4Cl as the solubilizer, water as the solvent and a certain amount of hydrochloric acid, thereby forming Sr-Cu bimetallic cooperative catalysis reaction systems for C2H2 dimerization. Under the optimum condition, the acetylene conversion is 13 % and monovinylacetylene selectivity can reach to 94 %.